Prevalence of Pneumonia Associated with Measles Among Infants and Children - Tayyaba Aslam, Shazra Azam, Iqbal Ahmad, Muhammad Irfan, Husnain Raza, Muhammad Gauhar Shabbir (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Measles remains a significant cause of childhood morbidity and mortality in developing countries, primarily due to its complications such as pneumonia. Despite the availability of an effective vaccine, suboptimal immunization coverage and malnutrition continue to contribute to measles outbreaks and severe clinical outcomes. Objectives: To determine the prevalence of pneumonia in children diagnosed with measles and to assess its association with age, gender, immunization status, and nutritional status. Study Design & Setting: A descriptive cross-sectional study conducted at the Pediatric Department of Shahida Islam Medical college Lodhran, over a six-month period. Methodology: A total of 120 children aged 0–12 years with clinically diagnosed measles were enrolled using non-probability consecutive sampling. Pneumonia was diagnosed based on WHO clinical criteria. Relevant demographic, clinical, nutritional, and immunization data were collected using a structured proforma. Statistical analysis was performed using SPSS version 25.0; p ≤ 0.05 was considered significant. Results: Pneumonia was observed in 72 (60.0%) children. Pneumonia prevalence was significantly higher in infants (38.9%), malnourished children (58.3%), and those who were either partially immunized (29.2%) or not immunized (45.8%) (p < 0.05). No significant association was found with gender. Conclusion: Pneumonia is a common and serious complication among children with measles, particularly in infants, malnourished, and unvaccinated individuals. Strengthening routine immunization and improving nutritional status are critical to reducing measles-related pneumonia. Keywords: Children, Immunization, Infants, Malnutrition, Measles, Pneumonia, Prevalence, Vaccination